Efektivitas Pemberian Air Rebusan Mahkota Dewa Terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi Di Kelurahan Hutuo Kecamatan Limboto Kabupaten Gorontalo - Madiko, Sri Olfi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective:One form of treatment for hypertension that is currently developing in society is herbal treatment. One of the herbal plants that is currently widely used to lower blood pressure is Mahkota dewa. The aim of this study was to determine the effectiveness of giving Mahkota Dewa boiled water to reduce blood pressure in elderly people with hypertension in the Hutuo sub-district. Methods:The research method used is Pre Experimental research, the planning used is One Group Pre test and Post test design. Results:The results obtained from this research were that in the group given the crown of god there was a change in the average systolic blood pressure during the pre-test and posttest, namely from 148 mmHg to 140,233 mmHg, while the average change in diastolic blood pressure was from 92 mmHg to 86,300 mmHg. Conclusion:From the results of statistical tests carried out to determine blood pressure before and after being given boiled water for Mahkota Dewa, the value of Sig. (2-tailed), namely p = 0.001, which means that there is an effect of boiled water on the crown of the gods on the blood pressure of elderly people who have hypertension. This can be influenced by the potassium content in the god's crown..